Comics integrated with Islamic values as a learning media to enhance student’s understanding - Siregar, Sa'adatun Nizwah; Adlini, Miza Nina (Universitas Wiralodra, 2025)
Media in learning greatly enhances the effectiveness of the learning process, presents information more engagingly, facilitates material interpretation and condenses information, for example, comic media. The research aims to develop comics integrated with Islamic values on digestive system material to improve understanding of Biology learning concepts. The research method used is Research and Development (R&D) with the ADDIE model. The results showed that the comics integrated with Islamic values on the material of the digestive system had passed the validation process by material experts, media experts, and Islamic integration experts with a validity percentage of 90% content eligibility, 93.3% language, and 80% presentation and 93.3% cover design, 96% content suitability, and an overall appearance of 80% from media validators and 93.4% for Islamic value integration. This comic is considered very practical based on the assessment of teachers and students on small-scale and large-scale trials, with a percentage of practicality of 93.3 from teachers, 80.66% of students on small-scale trials, and 78.14% on large-scale. The implementation of comics in Biology learning also proved to be quite effective, with an N-Gain of 0.58 included in the medium category. The conclusion of the development of comics integrated with Islamic values on the material of the digestive system effectively improves students' understanding of concepts, arousing interest and supporting the understanding of complex lesson concepts.